From Recognizing Characters to Understanding Characters —A Study on the Teaching Models and Evolution of Textbook Development in the Han Dynasty - Hao, Wang Shih (Journal of Ecohumanism, 2024)
The purpose of this paper was to explore the development of Han dynasty Chinese character learning materials, from the early Cang Jie Pian to later works like Shuo Wen Jie Zi, a classical text explaining Chinese characters. The study focused on the evolution of the texts and the teaching and understanding of Chinese characters over this period, particularly how the vocabulary used and the explanatory methods for characters developed. The findings indicated that the vocabulary in beginner character books changed alongside the times, as evidenced by literacy education and the recording of texts during the era. The study undertook a comprehensive examination of the use of common words during the Han dynasty to clarify the concepts surrounding the organization of characters. It also investigated how concepts of character attribute classification gradually developed into the radical-based and form-cluster thinking of Shuo Wen Jie Zi, showing that Han-era character learning materials adapted based on spoken language habits. This research sheds clearer light on the evolution of textual content and instructional modes within the historical development of Chinese character education.